2005
DOI: 10.1128/jvi.79.7.4347-4356.2005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Factors Control Efficiencies of Cell Entry, Efficacies of Entry Inhibitors, and Mechanisms of Adaptation of Human Immunodeficiency Virus

Abstract: Replication of human immunodeficiency virus type 1 (HIV-1) in diverse conditions limiting for viral entry into cells frequently leads to adaptive mutations in the V3 loop of the gp120 envelope glycoprotein. This has suggested that the V3 loop limits the efficiencies of HIV-1 infections, possibly by directly affecting gp120-coreceptor affinities. In contrast, V3 loop mutations that enable HIV-1 JR-CSF to use the low-affinity mutant coreceptor CCR5(Y14N) are shown here to have negligible effects on the virus-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
136
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 61 publications
12
136
1
2
Order By: Relevance
“…We began illumination simultaneously with raising temperature and DiD and NC-GFP mixing was completed within ϳ5 min (Figure 6). A reporter gene assay has shown that fusion of virus does not plateau for several hours (Platt et al, 2005) and photoaffinity labeling of SIV surface proteins upon fusion with cells indicated that fusion did not saturate for at least tens of minutes (Raviv et al, 2002). The faster saturation we observed is likely due to photo-induced inactivation.…”
Section: The Pseudoviral-cell Fusion Systemmentioning
confidence: 60%
“…We began illumination simultaneously with raising temperature and DiD and NC-GFP mixing was completed within ϳ5 min (Figure 6). A reporter gene assay has shown that fusion of virus does not plateau for several hours (Platt et al, 2005) and photoaffinity labeling of SIV surface proteins upon fusion with cells indicated that fusion did not saturate for at least tens of minutes (Raviv et al, 2002). The faster saturation we observed is likely due to photo-induced inactivation.…”
Section: The Pseudoviral-cell Fusion Systemmentioning
confidence: 60%
“…Specifically, VCV EC 50 values were ϳ 20 times higher in donors with ϳ 7 ϫ 10 3 CCR5 molecules/cell than in donors with ϳ 2 ϫ 10 3 CCR5 molecules/cell. Previous studies with cell lines have shown that CCR5 levels influence the antiviral activity of the CCR5 antagonist TAK-779, with higher CCR5 levels resulting in reduced antagonist activity (24)(25)(26). Ketas et al (27) have shown recently that donor variation in CCR5 levels (determined by mean fluorescence intensity) correlates with the antiviral activity of VCV.…”
Section: Discussionmentioning
confidence: 99%
“…In the RAPA/VCV combination, reduction of CCR5 density and partial blocking of CCR5 by VCV would effectively prevent CD4 bound viral envelopes from engaging sufficient CCR5 molecules. As a result, CD4-triggered envelopes unable to progress in the entry cascade would be exposed for prolonged periods of time and subjected to inactivation (24). We currently are investigating these mechanisms in an effort to characterize the basis for antiviral synergy by the RAPA/CCR5 antagonist combination.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, susceptibility to fusion inhibitors appears to be dependent on the affinity of gp120 for the coreceptors as well as on coreceptor density at the cell surface, both of which factors affect fusion kinetics (34). A faster fusion process will reduce the length of time during which the ENF molecular target is exposed, thus reducing the virus sensitivity to this inhibitor (28,30,34). We thus hypothesized that in patients failing ENF treatment, the biological properties of Env, and therefore the whole envelope genetic background, could influence the selection of ENF resistance mutations, thereby conditioning the emergence of ENF-resistant viruses.…”
mentioning
confidence: 99%